2020
DOI: 10.1002/solr.202000359
|View full text |Cite
|
Sign up to set email alerts
|

Improving Efficiency of Organic Solar Cells by Restricting the Rotation of Side Chain on Small Molecule Acceptor

Abstract: Herein, three carbazole‐based small molecule acceptors (SMAs), named 4TC‐4F‐C8C8, 4TC‐4F‐C6C8, and 4TC‐4F‐C16, are synthesized to study the influence of side chain conformation on SMAs. The three acceptors exhibit similar optical and electrochemical properties, but different crystallization properties. 4TC‐4F‐C16 shows a high crystallinity due to the small steric hindrance of linear n‐hexadecyl (C16) side chain. The large steric hindrance and free rotation for the 2‐hexydecyl (C6C8) side chain seriously distur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…[ 31 ] The large steric hindrance and free rotation for the side chains will disturb the intermolecular π–π stacking and lead to a low crystallinity. [ 55 ] Intermolecular aggregation often has a great influence on E b . for example, Wei et al [ 56 ] reported that the 3D packing crystal of the OSCs can effectively reduce E b with an extremely weak E b of 0.04 eV calculated in 4TIC.…”
Section: Effect Of the Structure Of Nfas On E B Of Excitonsmentioning
confidence: 99%
“…[ 31 ] The large steric hindrance and free rotation for the side chains will disturb the intermolecular π–π stacking and lead to a low crystallinity. [ 55 ] Intermolecular aggregation often has a great influence on E b . for example, Wei et al [ 56 ] reported that the 3D packing crystal of the OSCs can effectively reduce E b with an extremely weak E b of 0.04 eV calculated in 4TIC.…”
Section: Effect Of the Structure Of Nfas On E B Of Excitonsmentioning
confidence: 99%
“…This favorable stacking is beneficial to both the hole and electron transport, which will contribute to the higher FF. 36 Consequently, an outstanding PCE of 14.11% is achieved by the C8C8−4Cl-based OSCs with a V oc of 0.818 V, a J sc of 23.8 mA cm −2 , and an FF of 72.5%. It should be noted that our result is one of the best values ever reported in A−D−A′−D− A-type NFREAs (Figure S5).…”
Section: Optical and Electrochemicalmentioning
confidence: 97%
“…This has a large influence on the PV performance in blends with the donor PBTIBDTT. The best PCE is achieved with α-branched 9-7 (12.1%), the lowest with the β-branched 9-8 (2.38%) …”
Section: Nine Fused Aromatic Ring Systemsmentioning
confidence: 98%
“…The best PCE is achieved with αbranched 9-7 (12.1%), the lowest with the β-branched 9-8 (2.38%). 537 Compound 9-10 (DTTC-4F) is very similar to 9-7, with the only difference being the use of octylphenyl instead of hexylphenyl side chains on the central core. 538 Solar cells with PM6 gave PCE values of almost 14%.…”
Section: Eight Fused Aromatic Ring Systemsmentioning
confidence: 99%